Meta-analytical study on forage production of natural grasslands in Rio Grande do Sul (Semiárida, 2020)
Primary production in natural pastures in Rio Grande do Sul (RS) is directly related to environmental conditions and management of the pasture that is being submitted. The aim of this study was to characterize and analyze possible relationships not apparent, through meta-analysis, using data from forage production from nine experiments, conducted between 2000 and 2012 in rangelands in RS. The database consisted of 208 observations, originating from experiments performed on three different physiographic regions of the state. The variables used were herbage mass (MF), forage allowance (OFR) and forage accumulate rate (TAD). The data were processed by vectorial amplitude and subjected to multivariate analysis of clusters, randomization and ordination using the Euclidean distance as similarity measure. The MF and OFR variables were similar and higher correlation (R = 0.85) with axis I of the ordination of sample units, which explained most of the variation in results (49.59%). MF were different among the three groups (3469, 1743 and 1403 kg. ha-1 respectively for groups 1, 2 and 3). TAD of groups 1 and 3 was similar (12.4 kg.ha-1.day-1) (P= 0.49) and higher than in group 2. OFR in groups 2 and 3 was similar (13.4 kg DM per 100 kg LW) and lower than in group 1 (30.8 kg DM per 100 kg LW). The analysis revealed distinct groups formed for the MF and TAD may result in similar OFR.
Keywords: Multivariate analysis; Forage allowance; Forage accumulate rate; Natural grasslands; Rio Grande do Sul; Brazil